High-Throughput Assessment of Drug Cardiac Safety Using a High-Speed Impedance Detection Technology-Based Heart-on-a-Chip - Xi Zhang; Tianxing Wang; Ping Wang; Ning Hu (Micromachines, 2016)
Drug cardiac safety assessments play a significant role in drug discovery. Drug-induced cardiotoxicity is one of the main reasons for drug attrition, even when antiarrhythmic drugs can otherwise effectively treat the arrhythmias. Consequently, efficient drug preclinical assessments are needed in the drug industry. However, most drug efficacy assessments are performed based on electrophysiological tests of cardiomyocytes in vitro and cannot effectively provide information on drug-induced dysfunction of cardiomyocyte beating. Here we present a heart-on-a-chip device for evaluating the drug cardiac efficacy using a high-speed impedance detection technology. Verapamil and doxorubicin were utilized to test this heart-on-a-chip, and multiple parameters of cardiomyocyte beating status are used to reveal the effects of drugs. The results show that drug efficacy or cardiotoxicity can be determined by this heart-on-a-chip. We believe this heart-on-a-chip will be a promising tool for the preclinical assessment of drug cardiac efficacy.